Triple-negative breast cancer: Pattern of recurrence and survival outcomes - Shyny Reddy Chintalapani; Stalin Bala; Meher Lakshmi Konatam; Sadashivudu Gundeti; Siva Prasad Kuruva; Monalisa Hui (Indian Journal of Medical and Paediatric Oncology)
Introduction: Triple-negative breast cancer (TNBC) is a subtype of breast cancer which is defined as the absence of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 overexpression by immunohistochemistry. As the survival data on TNBC in the Indian population are scant, this study was done to analyze the clinicopathological features and clinical outcomes of TNBC patients. Materials and Methods: Data from medical records of patients with breast cancer between 2009 and 2014 were retrieved, and patients with TNBC were identified and analyzed for demographic and clinicopathological features. Survival analyses were performed using the Kaplan–Meier method for disease-free survival (DFS) and overall survival (OS). Results: A total of 1024 breast cancer patients were registered at our institute during the study period, of which 198 were TNBCs accounting for 19.3% of all breast cancers. Median age at the diagnosis was 50 years (range, 22–78 years). Lymph nodal positivity in TNBC was associated with larger tumor size (P = 0.003) and higher tumor grade (P = 0.01). At a median follow-up of 48 months (range, 12–88), 36 (19.1%) patients had recurrence of the disease, whereas 28 (14%) patients were lost to follow-up. Lung (52.7%) was the most common site of recurrence followed by bone (25%) and brain (11.1%). Three-year DFS and OS were 63.2% and 65.6%, respectively. On univariate analysis, nodal status, size of tumor, and lymphovascular invasion were found to have a significant impact on OS and DFS. On multivariate analysis, only nodal status was significant for DFS and OS (P < 0.001 and P = 0.001, respectively). Conclusions: TNBCs have a rapid clinical course, and early recurrences are common inspite of timely medical intervention which reflects the aggressive tumor biology. This warrants further studies on intensification of chemotherapy and identification and development of targeted therapy aimed at decreasing recurrences and improving survival in this patient population.